THE USE OF SOCIAL DEIXIS IN INI TALK SHOW - Kiki Zakiyyah (ReALL - Research on Applied Linguistics and Literature, 2022)
The research entitled â€œThe Use of Social Deixis in Ini Talk Showâ€ aims to find social deixis used by the participants of Ini Talk Show NET.TV and to find out inappropriate function of social deixis in the talk show. The researcher analyzed the data from two episodes of the talk show using the theory of social deixis from Levinson (1983). This research used qualitative descriptive method and the data collection techniques were observation and documentation. The result showed that from 88 data, there were 67 relational social deixis and 21 absolute social deixis. In addition, there were four inappropriate functions of social deixis. The factors of inappropriate function of social deixis usage are the relationship among the communicator and the type of the program that consists of humor. The researcher suggested for the next researcher to investigate other kinds of television program using the theory of social deixis from Levinson (1983). The researcher hopes this research will be one of references in doing similar research.